Borrowing on the Wrong Credit Card? Evidence from Mexico - Ponce, Alejandro; Seira, Enrique; Zamarripa, Guillermo (American Economic Review, 2017)
We establish new facts about the way consumers allocate debt among their credit cards using data for a representative sample of cardholders in Mexico. We find that relative prices are weak predictors of the allocation of debt, purchases, and payments. Consumers allocate a large fraction of their debt to high-interest cards, incurring a cost of 31 percent above the minimum. Using an experiment, we find that consumers do not substitute in the price margin, although they respond to salient temporary low-interest offers. We conclude that limited attention and mental accounting best rationalize our results and discuss implications for the market. (JEL D14, G21, O12, O16)